Habitus and Change: Phenomenological Insights into Curriculum Adaptation in Indonesian Islamic Schools - Eka Rizki Amalia; Muhammad Yuliansyah; Yhasinta Agustyarini; Muqimah Liwais Sunnah; Juli Amaliya Nasucha; Nurul Azizah Ria Kusrini (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
Indonesia’s education system is undergoing a significant transformation with the introduction of a new curriculum. This shift presents unique challenges for Islamic schools (madrasahs), where school leaders must reconcile national education goals with religious principles, all while navigating systemic constraints and limited resources. This study uses Bourdieu’s theoretical framework to examine how Heads of Curriculum (HoCs) respond to these challenges through their leadership strategies. Employing a qualitative phenomenological approach, the study investigates the lived experiences of six HoCs from different madrasahs through semi-structured interviews. Thematic analysis, grounded in Bourdieu’s concepts of habitus, field, and capital, reveals how internal dispositions and systemic influences shape leadership behaviour. The findings show that the HoCs developed adaptive strategies that reflect key themes: leadership and adaptability, resourcefulness and social capital, balancing Islamic values with reform objectives, and navigating policy disparities. These strategies highlight how habitus, shaped by cultural, professional, and systemic experiences, guides leadership practices that balance tradition with modern reform. Ultimately, the study offers valuable empirical insights into curriculum reform in Islamic education and extends Bourdieu’s framework by integrating cultural and religious contexts, showing how school leaders convert structural limitations into opportunities for institutional growth.